Kepatuhan Penggunaan Safety Belt Studi Kasus Dosen Universitas Islam Riau Pekanbaru - Abdul Kudus Zaini; Astuti Boer; Muhammad Irvan (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Safety Seat belts effectively prevent car users from being injured in an accident. However, it is felt that its use has not been fully complied with by car users, depending on the awareness of the car user. The study of compliance with the use of cars in wearing seat belts was conducted to determine the characteristics that affect compliance. Primary data were obtained by conducting interviews, recording compliance with the use of seat belts with direct calculations, and speed studies. The method used in this research is quantitative and qualitative methods using primary data resulting from the random distribution of questionnaires to lecturers at the Islamic University of Riau which is then analyzed with statistical data analysis software. The safety belt compliance of the Riau Islamic University lecturers is good. Most of them are drivers, aged around 35 - 55 years, high income, and have a valid driver's license. Almost everyone understands about setting seat belts, is aware of road safety, and agrees that seat belts should be worn while the car is moving. Drivers are more obedient than front seat passengers, both on urban roads and outside cities. For people who have a driver's license, safety is the reason for compliance. People who drive around the city are more obedient than people who live outside the city. There is a significant relationship between compliance with the use of seat belts with driving speed. On arterial roads, motorists who drive at high speeds tend to be more careful and obey the rules. While on collector roads, drivers who slow down are more obedient to the rules. Meanwhile, front seat passengers will be more obedient in using seat belts if the car is moving fast.